KEANEKARAGAMAN JENIS TEGAKAN PADA KAWASAN HUTAN LINDUNG PADANG TIKAR KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - Nugraha, Adji Fatur; Fahrizal, .; M, Iskandar A (Universitas Tanjungpura, 2019)
Protection forest has high diversity, one of them is Padang Tikar protection forest, Kubu Raya Regency. Recently, there is no data regarding stand species diversity in Padang Tikar protection forest. This research aimed to find out stand species diversity in Padang Tikar protection forest. By using survey method with sampling technique, a combination of lane and striped plot method, measuring plot was made continously on the lane. The width of the Padang Tikar protection forest is 33,000 Ha. Lane was put purposively and following on satellite imagery of earth, where the lane are put cutting the way the river flow. The area of observation was 6 Ha wide, the number of observation lanes were three with the size of 20 x 100 metres each, two lanes were on the west side of the protection forest and one lane on the east side, with the length of 3 km. Three lanes were chosen due to the area was almost similar in. The distance between lanes was 200 metres. The total amount of plot observed were 30 plots. Research results showed that there were 40 stand species in the area of the Padang Tikar protection forest. Importance Value Index showed there were dominant plants, tree level which are resak (Vatica celebensis brandis), nyatoh (Palaquium pseudocuneteum), meranti (Shorea parvifolia dyer), bintangur (Callophylum inophloide king), ubah (Zygigium sp), and medang (Litsea firma) with the Importance Value of 170,01%.Keyword : Diversity, Batu Ampar, Forest Protected, Padang Tikar.